Cardiorespiratory Responses to Glittre ADL Test in Bronchiectasis: A Cross-Sectional Study. (17th December 2018) - Hena, Ravoori; Alaparthi, Gopala Krishna; Shyam Krishnan, K.; Anand, R.; Acharya, Vishak; Acharya, Pretham
Abstract : Background . Bronchiectasis is a chronic respiratory condition characterised by chronic sputum production, fatigue, and dyspnoea. These symptoms will lead to reduced exercise capacity and a reduced ability to carry out activities of daily living. Glittre ADL test is a valid and reliable test which evaluates the activities of daily living. Aim . To investigate whether the Glittre ADL test can differentiate the functional capacity and cardiorespiratory responses of patients with bronchiectasis from those healthy individuals using the six-minute test as a functional performance standard. Methods . This study included 30 subjects: 15 bronchiectasis and 15 age- and gender-matched healthy subjects. The patients and healthy subjects were made to perform the Glittre ADL and six-minute test on two consecutive days. Parameters such as time taken, distance walked, HR, RR, SpO2, and dyspnoea were recorded before and after the tests. Results . The performance of bronchiectasis was worse than the healthy group on the Glittre ADL test (4.78 ± 1.33 min, 3.94 ± 0.82 min, p = 0.04 ). Distance walked in the six-minute walk test by the bronchiectasis was 42 meters lesser than the healthy (400.33 ± 77.99, 442 ± 89.21, p = 0.18 ). The Glittre ADL test was correlated with 6MWT when the total sample was analysed (r = − 0.41, p = 0.05 ). There was moderate positive correlation between heart rate variation, dyspnoea, respiratory rate, and peripheral saturation (SpO2 ) between the tests (Glittre heart rate versus six-minute walk test heart rate (r = 0.55, p = 0.001 ); Glittre (Borg) versus six-minute walk test (Borg) (r = 0.72, p = 0.00 ); Glittre respiratory rate versus six-minute walk test RR (r = 0.62, p = 0.00 ); Glittre SpO2 versus six-minute walk test SpO2 (r = 0.40, p = 0.02 )). The bronchiectasis group had a statistically significant higher (p = 0.08, p = 0.46 ) increase in dyspnoea and RR than the controls in both the Glittre ADL test and six-minute walk test (p = 0.009, p = 0.03 ), with the similar HR variation in both the groups (p > 0.05 ). There was statistical difference in peripheral oxygen saturation in bronchiectasis in the six-minute walk test (p = 0.03 ). Conclusion . The Glittre ADL test induced similar cardiorespiratory responses when compared to the six-minute walk test. So, the Glittre ADL test can be used as an assessment tool besides the six-minute walk test for the more complete evaluation of functional capacity and activities of daily living.